Positional income concerns and personality: evidence from Germany. Issue 14 (16th August 2018) - Friehe, Tim; Mechtel, Mario; Pannenberg, Markus
ABSTRACT: Positional income concerns (PIC) strongly influence economic behaviour and life outcomes. However, very little is known about the underlying heterogeneity regarding their importance across individuals on the one hand and across different reference groups on the other. Our analysis builds on representative survey data reporting PIC vis-à-vis seven reference groups, allowing us to identify marked heterogeneity both between and within subjects. We present evidence about who (in terms of personality) compares to whom (in terms of reference group).